Community Schools : Designing for Sustainability, Wellbeing and Inclusion. - Taylor, Helen (Architect) (Milton : RIBA Publications, 2023)
Schools have the potential to empower communities by connecting people better with the places they live. But how can these benefits be baked into a design brief?
Cover -- Half Title -- Title -- Copyright -- Contents -- Acknowledgements -- About the Authors -- Introduction -- Chapter 1 A Different Approach to School Design -- The Case for Change -- Chapter 2 Designing for the Community -- Chapter 3 Designing for Wellbeing -- Chapter 4 Designing for Connectivity and Inclusion -- Chapter 5 Indicators and Evaluation -- Chapter 6 A New Brief for Community Schools -- Designing for Sustainability, Wellbeing and Inclusion -- Bibliography -- Endnotes -- Index -- Image Credits
Description based upon print version of record.
Keywords: ARCHITECTURE / Public, Commercial, or Industrial Buildings; ARCHITECTURE / General; School buildings; Community schools